IoT and Data Security - Vinay Michael; Jubilant J Kizhakkethottam (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Internet of Things (IoT) is a collection of network devices, which are predominantly used to collect, store and exchange data over the network. Security in IoT deals with the threats and the breaches, which organization is facing through its network devices. Observing, Spotting, and safeguarding is also coming under the umbrella of IoT security. In this paper provides a comprehensive analysis of possible security threats facing the IoT and suggests its viable solutions to solve the problem.